The ten most influential churches of the past century: how they impact you today - Towns, Elmer L. (Destiny Image Publishers, 2014)
Part One : The 10 most influential churches. 1. The spread and growth of Pentecostalism worldwide ; Apostolic Faith Mission, Los Angeles, California (The Azusa Street Revival) -- 2. The unseen but ever-present influence of house churches ; Chinese Organic House Churches, Mainland China -- 3. A non-violent revolution that led to racial integration in churches ; Ebenezer Baptist Church, Atlanta, Georgia -- 4. Home cells used for church ministry and outreach ; The Yoido Full Gospel Church, Seoul, South Korea -- 5. A church built on Sunday School evangelism ; First Baptist Church, Dallas, Texas -- 6. A change to Bible teaching instead of traditional pulpit ministry ; Scofield Memorial Church, Dallas, Texas -- 7. A seeker-model church designed for the unchurched ; Willow Creek Community Church, South Barrington, Illinois -- 8. A new church culture initiated by Baby Boomers ; Calvary Chapel, Costa Mesa, California -- 9. Initiating praise-worship in worship services ; Hillsong Church, Sydney, Australia -- 10. Using media and marketing to extend the influence of a church ; Thomas Road Baptist Church, Lynchburg, Virginia -- -- Part Two : Other churches and trends. 11. Bible teaching for every age through Sunday School ; First Presbyterian Church, Hollywood, California -- 12. The influence of positive thinking and financial prosperity on churches ; Crystal Cathedral, Garden Grove, California -- 13. Churches built on a systematic approach to personal soul-winning ; Coral Ridge Presbyterian Church, Coral Ridge, Florida -- 14. Churches organized and focused as foreign mission endeavors ; The People's Church, Toronto, Canada -- 15. An aggressive initiative of servanthood evangelism ; Vineyard Church, Cincinnati, Ohio -- 16. A church-planting strategy of evangelism ; Northwood Church, Keller, Texas -- 17. A multisite church meeting in multiple locations ; Jotabeche Methodist Pentecostal Church, Santiago, Chile -- 18. A leadership church that influenced a large denomination ; Young Nak Presbyterian Church, Seoul, South Korea -- 19. A video-venue multisite church ; Seacoast Church, Greater Charleston, South Carolina -- 20. An international interactive congregation built on the internet ; Glory of Zion International Ministries, Corinth, Texas -- Afterthought : What can we learn from these churches? -- Appendix. A. Research techniques to find the 10 churches of greatest influence -- B. The 10 greatest leadership-influencers in Christian ministry in the past 100 years -- C. The 15 greatest influences of Christian thought in the past 100 years